SISTEM PESAWAT TANPA AWAK MENGGUNAKAN KAMERA THERMAL UNTUK MEMBANTU PENCARIAN KORBAN BENCANA ALAM - I Gede Feryanda Frasiska; Ir. I Nyoman Budiastra, MKes., MT; Pratolo Rahardjo, S.T.,M.T. (Program Studi Teknik Elektro UNUD, 2020)
In Indonesia, the weather is influenced by seasons, namely the dry season and the rainyseason. Apart from weather, natural disasters can also occur due to the earth's tectonicpatterns, either in the form of tsunamis or earthquakes. Every natural disaster will have adetrimental impact on society both economically and socially. The impact of a disaster like anearthquake is the collapse of buildings. Collapsed buildings due to earthquakes can leave largenumbers of people dead or buried in the rubble. The evacuation process of post-disaster victimsmust be carried out immediately to reduce the risks posed by the disaster, such as the numberof casualties caused by delays in the evacuation process. Based on these problems,researchers are motivated to create a technological innovation that can help the SAR team iinthe processs of detecting victims from debris through the air by detecting the victims bodytemperature, the number of victims and showing the coordinates of the victim's position.disaster victims. The tool is called DROPBA, which is an Unmanned Aircraft System or UAVthat uses thermal cameras to help search for victims of natural disasters. The SAR team at thepost will control DROPBA or Unmanned Aircraft to detect disaster victims who are in the wreck,and inform the SAR team information wirelessly in the form of a path to the position of thedisaster victim. The design results are in the form of a 3-dimensional model image from the DROBA tool and the components and camera systems used are a thermal camera connectedto the Raspberi pi system and image processing using Open CV.